SPEECH ACTS ANALYSIS IN A SHORT JAVANESE CONVERSATION AT THE CLASSROOM - Sarah Sumponogati . (Universitas Stikubank (UNISBANK) Semarang, 2018)
Illocutionary acts is one of speech act types which means a speaker’s purpose in speaking is not merely to produce utterance that have an intended meaning. This study is aimed at finding the speech act types and illocutionary acts types used in the short Javanese conversation recorded by the researcher. This research is designed in descriptive qualitative. The procedure of analyzing the utterances is based on the criteria proposed by Searle (1997). The results show that the utterances produced by the students involved are mostly using assertive, followed by directive and commissive. There is no expressive and declaration illocutionary actperformed in the conversation.Key Words: Conversation, utterance, speech acts,illocutionary acts.